Solving Fuzzy Linear Programming as Multi Objective Linear Programming Problem - Princy Flora, M. (Asian Journal of Science and Applied Technology, 2016)
The constraints and the objective function of the fuzzy linear programming problem are converted into the multi-objective optimization problem (i.e.,) into an equivalent crisp linear problem.Finally, the multi-objective linear programming problem is converted into the weighted linear programming problem to show that they are independent of weights and obtained the complete optimal solution.